Glycoconjugate vaccines: some observations on carrier and production methods. Issue 2 (3rd July 2019) - MacCalman, Thomas E.; Phillips-Jones, Mary K.; Harding, Stephen E.
ABSTRACT: Glycoconjugate vaccines use protein carriers to improve the immune response to polysaccharide antigens. The protein component allows the vaccine to interact with T cells, providing a stronger and longer-lasting immune response than a polysaccharide interacting with B cells alone. Whilst in theory the mere presence of a protein component in a vaccine should be sufficient to improve vaccine efficacy, the extent of improvement varies. In the present review, a comparison of the performances of vaccines developed with and without a protein carrier are presented. The usefulness of analytical tools for macromolecular integrity assays, in particular nuclear magnetic resonance, circular dichroism, analytical ultracentrifugation and SEC coupled to multi-angle light scattering (MALS) is indicated. Although we focus mainly on bacterial capsular polysaccharide-protein vaccines, some consideration is also given to research on experimental cancer vaccines using zwitterionic polysaccharides which, unusually for polysaccharides, are able to invoke T-cell responses and have been used in the development of potential all-polysaccharide-based cancer vaccines. A general trend of improved immunogenicity for glycoconjugate vaccines is described. Since the immunogenicity of a vaccine will also depend on carrier protein type and the way in which it has been linked to polysaccharide, the effects of different carrier proteins and production methods are also reviewed. We suggest that, in general, there is no single best carrier for use in glycoconjugate vaccines. This indicates that the choice of carrier protein is optimally made on a case-by-case basis, based on what generates the best immune response and can be produced safely in each individual case. Abbreviations : AUC: analytical ultracentrifugation; BSA: bovine serum albumin; CD: circular dichroism spectroscopy; CPS: capsular polysaccharide; CRM197: Cross Reactive Material 197; DT: diphtheria toxoid; Hib: Haemophilius influenzae type b; MALS: multi-angle light scattering; Men: Neisseria menigitidis ; MHC-II: major histocompatibility complex class II; NMR: nuclear magnetic resonance spectroscopy; OMP: outer membrane protein; PRP: polyribosyl ribitol phosphate; PSA: Polysaccharide A1; Sa: Salmonella ; St.: Streptococcus ; SEC: size exclusion chromatography; Sta: Staphylococcus ; TT: tetanus toxoid; ZPS: zwitterionic polysaccharide(s).